Social Attention and Emotional Responsiveness in Young Adults With Autism - Dijkhuis, Renee; Gurbuz, Emine; Ziermans, Tim; Staal, Wouter; Swaab, Hanna (Frontiers in Psychiatry, 2019)
Children with autism spectrum disorder (ASD) are generally characterized by marked impairments in processing of social emotional information, but less is known about emotion processing in adults with the disorder. This study aimed to address this by collecting data on social attention (eye tracking), emotional arousal (skin conductance level; SCL) and emotional awareness (self- report) in a paradigm with social emotional video clips. 52 young, intelligent adults with ASD (IQrange = 88 - 130, Agerange = 18 - 24) and 31 typically developing (TD) ASD (IQrange = 94 - 139, Agerange = 19- 28) gender matched controls participated, and reported on severity of autism symptoms (SRS-A). Results showed no group difference in social attention, while autism symptom severity was related to decreased attention to faces across participants (r = -.32). Average SCL was lower in the ASD group, but no group difference in arousal reactivity (change from baseline to emotional phases) was detected. Lower SCL during video clips was related to autism symptom severity across participants (r = -.29). ASD individuals reported lower emotional awareness. We conclude that, even though no deviations in social attention or emotional reactivity were found in ASD, an overall lower level of social attention and arousal may help explain difficulties in social functioning in ASD.